Mental health change in the transition to permanent supportive housing: The role of housing and social networks. Issue 8 (17th August 2019) - Harris, Taylor; Rhoades, Harmony; Duan, Lei; Wenzel, Suzanne L.
Abstract: Aims: Permanent Supportive Housing (PSH) may improve homeless adults' mental health via housing stabilization and/or improved relational factors, however, the role of housing and social networks on PSH residents' mental health change is minimally understood. Methods: Interviews were conducted with a baseline sample of adults experiencing homelessness ( N  = 421), across their initial year in PSH (3‐months, 6‐months, and 12‐months). Generalized linear mixed models assessed changes in positive past‐month psychiatric disability screenings (Modified‐Colorado Symptom Index [MCSI]) and probable posttraumatic stress disorder (PC‐PTSD) in controlled models, and between and within‐subject effects of time‐varying social network correlates on mental health changes. Results: Compared with baseline, positive MCSI screens continuously decreased over time (56%, 54%, and 50%) while PC‐PTSD screens declined initially (40%) with marginal decreases at remaining follow‐ups (39% and 38%). These differences remained significant in controlled models. Gaining a romantic partner was associated with a longitudinal increase in a positive MCSI screening. Between subjects, emotional health counselors and conflicting network members were associated with an increased likelihood in positive screenings, while doctors and case managers were protective. Conclusion: Housing may facilitate positive changes in PSH residents' mental health, yet positive screenings remain high. Social network interventions that increase residents' positive interpersonal exchanges and prosocial relationships are warranted.